1. (a+2b)²-(3c+4d)²=
2. (m-2n)²-(2p-3q)²=
3. 9(m+n)²-(m-n)²=
4. 16(a+b)²-9(x+y)²=
5. (x-y)²-(m+n)²=
6. (2a-3c)²-(4b+5d)²=
7. 4(a-b)²-(a+b)²=
8. 9(a-b)²-4(x-y)²=

1

Ответы и объяснения

2014-01-29T18:01:42+04:00
1. (a+2b)²-(3c+4d)²=a²+4ab+4b²-9c²-24cd-16d²
2. (m-2n)²-(2p-3q)²=m²-4mn+4n²-4p²+12pq-9q²
3. 9(m+n)²-(m-n)²=9(m²+2mn+n²)-m²+2mn-n²=9m²+18mn+9n²-m²+2mn-n²=8m²+20mn+8n²
4. 16(a+b)²-9(x+y)²==16(a²+2ab+b²)-9(x²+2xy+y²)=16a²+32ab+16b²-9x²-18xy-9y²
5. (x-y)²-(m+n)²=x²-2xy+y²-m²-2mn-n²
6. (2a-3c)²-(4b+5d)²=4a²-12ac+9c²-16b²-40bd-25d²
7. 4(a-b)²-(a+b)²=4(a²-2ab+b²)-a²-2ab-b²=4a²-8ab+4b²-a²-2ab-b²=3a²-10ab+3b²
8. 9(a-b)²-4(x-y)²=9(a²-2ab+b²)-4(x²-2xy+y²)=9a²-18ab=9b²-4x²+8xy-4y²